Is obesity a risk factor for extended length of stay and readmission after total hip arthroplasty? - Richard, Brian; Reilly, Austin; Lyden, Elizabeth; Garvin, Kevin (Annals of Joint; Vol 3 (September 2018): Annals of Joint, 2018)
Background: The burden of hospital length of stay and readmission rates for total hip arthroplasty patients has been scrutinized as a source of potentially preventable cost. Attempts to determine and minimize the risks for increased length of stay and readmission rates have focused on patients’ comorbidities, particularly obesity. While many studies have demonstrated obesity’s connection with total hip arthroplasty complications, there is conflicting data on obesity’s effect on length of stay and readmission rates. The purpose of this case-control study was to determine if obesity was independently associated with greater odds of increased length of stay and readmission rates when compared with other comorbidities. Methods: A total of 1,433 surgeries performed in 1,265 patients from our institution (622 males, 811 females) were studied. Readmissions were defined as any cause re-hospitalization within 90 days. Analysis of variables was used to determine which patient demographics and comorbidities were associated with body mass index. Odds ratios for risk of readmission and increased length of stay (≥5 days) were calculated for each body mass index category and possible confounders. Multivariable logistic regression with backward elimination was used to examine body mass index ≥40 and ≥50 as independent risk factors after adjusting for the possible confounders. All tests with a P value